Effects of Dexmedetomidine as an Adjuvant in Preoperative Ultrasound-Guided Internal Branch of Superior Laryngeal Nerve Block on Postoperative Sore Throat and Hemodynamics in Patients With Double-Lumen Endotracheal Intubation: A Randomized Controlled Trial - Chen Z; Zhang L; Lu G; Zhang Y; Zhao D; Zhao S; Zhang H; Jin Y; Zhao X; Jin Y (Journal of Pain Research)
Zheping Chen,1– 3,* Le Zhang,2,3,* Guodong Lu,2,3 Yizheng Zhang,2,3 Dexu Zhao,2,3 Shanshan Zhao,2,3 He Zhang,2,3 Yuelong Jin,4 Xin Zhao,2,3 Yanwu Jin2,3 1Shanghai Key Laboratory of Anesthesiology and Brain Functional Modulation, Translational Research Institute of Brain and Brain-Like Intelligence, Clinical Research Center for Anesthesiology and Perioperative Medicine, Department of Anesthesiology and Perioperative Medicine, Shanghai Fourth People’s Hospital, School of Medicine, Tongji University, Shanghai, 200434, People’s Republic of China; 2Department of Anesthesiology, The Second Hospital, Cheeloo College of Medicine, Shandong University, Jinan, 250033, People’s Republic of China; 3The second Clinical College of Shandong University, Jinan, 250033, People’s Republic of China; 4Department of Epidemiology and Health Statistics, School of Public Health, Wannan Medical College, Wuhu, 241001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xin Zhao; Yanwu Jin, Department of Anesthesiology, The Second Hospital, Cheeloo College of Medicine, Shandong University, 247 Bei Yuan Street, Jinan, 250033, People’s Republic of China, Email lujnzx@sohu.com; jinyanwu_aa@163.comBackground: Postoperative sore throat (POST) is a significant adverse effect after endotracheal intubation, especially with double-lumen endotracheal tubes (DLTs). Ultrasound-guided internal branch of the superior laryngeal nerve block (US-guided iSLNB) presents a potential intervention for POST. In this first randomized controlled trial to date, we aimed to investigate the effects of US-guided iSLNB, with or without perineural dexmedetomidine, on the incidence and severity of POST following DLTs.Methods: A total of 159 patients were randomly assigned to three groups: control, bilateral US-guided iSLNB (2 mL 0.20% ropivacaine + 1 mL saline on each side), and bilateral US-guided iSLNB combined with perineural dexmedetomidine group (2 mL 0.20% ropivacaine + 1 mL 0.5 μg·kg− 1 dexmedetomidine on each side). The incidence and severity of POST, hemodynamic fluctuations during intubation and extubation, the incidence and severity of cough and agitation during extubation, and perioperative complications were assessed. The primary outcome was the incidence of POST at 6 h after surgery.Results: Compared with the control group, preoperative US-guided iSLNB significantly reduced the incidence and severity of POST at 1 and 6 h after surgery, mitigated the incidence and severity of cough during extubation, and attenuated hemodynamic responses, including heart rate, mean arterial pressure, and rate-pressure product during intubation, 1 min after intubation, and 1 min after extubation (all P < 0.01). Compared with US-guided iSLNB alone, the combination of US-guided iSLNB with perineural dexmedetomidine reduced the incidence and severity of POST at 1, 6, and 12 h, as well as coughing during extubation (all P < 0.01). However, it demonstrated little effect on hemodynamics (all P > 0.05). No significant perioperative complications were observed in the three groups (all P > 0.05).Conclusion: Preoperative US-guided iSLNB combined with perineural dexmedetomidine effectively reduced the incidence, severity, and duration of POST and cough during extubation. No additional hemodynamic benefits were observed.Clinical Trial Registration: Chinese Clinical Trial Registry (ChiCTR2200061001).Keywords: dexmedetomidine, superior laryngeal nerve, sore throat, cough, hemodynamics